The Impact of Peer-Group Communication and Social Media Use on Students' Characters - Aminullah, Muhammad; Astawinetu, Erwin Dyah; Saputra, Nanda; Al Mahdi, Al Mahdi (Universitas Negeri Malang, 2022)
The purpose of this study is to investigate (1) the effect of peer group communication on students' morals and (2) the effect that social media use has on students' values. This study was carried out in the Pancur Batu District of North Sumatra Province's Deli Serdang Regency, Indonesia. Our population was 1,207 Muslim students at the state junior high school in the Pancur Batu District, Indonesia. In the end, we selected 300 students as our samples using the proportional stratified random sampling technique. For the research instrument, we employed a questionnaire that was developed to collect information regarding peer group communication and the use of social media among junior high school students in Pancur Batu, Deli Serdang, Indonesia. Path analysis was used to analyze and synthesize research data. The analysis results showed that (1) peer group communication directly affects students' morals, with a path coefficient of 0.179, and (2) the use of social media directly affects students' morals, with a path coefficient of 0.213